Measuring the Competitiveness and Efficiency of Indonesian Non-Oil and Gas Exports to Non-Traditional Markets - Hotsawadi, Hotsawadi; Gea, Imelda Veronica (JURNAL HUBUNGAN LUAR NEGERI, 2024)
In order to improve the performance of the trade balance, Indonesia is currently always trying to diversify the market through the expansion of export markets to non-traditional countries. For this reason, measuring competitiveness and export efficiency is crucial to be researched first. This study aims to measure the competitiveness and efficiency of Indonesia's Non-Oil and Gas Exports to Non-Traditional Markets by using the analysis methods RCA, EPD, X-Model and Stochastic Frontier Analysis with Gravity Model (SFGM). The results of the analysis show that based on the results of the competitiveness analysis (RCA) and export performance using EPD and X-Model, it shows that the competitiveness of Indonesia's non-oil and gas exports to non-traditional countries is still low or below global competitiveness. Meanwhile, the results of estimation using the Stochastic Frontier Analysis approach with the Gravity Model (SFGM) show that the variables of GDP of non-traditional countries, the number of population of non-traditional countries, Indonesia's GDP, competitiveness (RCA) and the area of non-traditional countries have a positive and significant effect on Indonesia's exports. Meanwhile, economic distance is estimated to have a negative and significant influence on Indonesia's non-oil and gas exports.